Efficacy of Hypnosis-Based Treatment in Amyotrophic Lateral Sclerosis: A Pilot Study - Palmieri, Arianna; Kleinbub, Johann R.; Calvo, Vincenzo; Sorarù, Gianni; Grasso, Irene; Messina, Irene; Sambin, Marco (Frontiers in Psychology, 2012)
Background: Amyotrophic lateral sclerosis (ALS) and its devastating neurodegenerative consequences have an inevitably psychological impact on patients and their caregivers: however, although it would be strongly needed, there is a lack of research on the efficacy of psychological intervention. Our aim was to investigate the effect of hypnosis-based intervention on psychological and perceived physical wellbeing in patients and the indirect effect on caregivers. Methods: We recruited 8 ALS volunteers patients as a pilot sample for an hypnosis intervention and self-hypnosis training protocol lasting one month. Anxiety and depression level was measured in patients and caregivers at pre and post treatment phase. Quality of life and perceived physical symptoms changes were also investigated in patients. Results: One month pre-post treatment improvement in depression, anxiety and quality of life was clearly clinically observed and confirmed by psychometric analyses on questionnaire data. Moreover, decreases in physical symptoms such as pain, sleep disorders, emotional lability and fasciculations were reported by our patients. Improvements in caregiver psychological wellbeing, likely as a consequence of patients psychological and perceived physical symptomatology improvement, were also observed. Conclusions: To the best of our knowledge, even if at a preliminary level, this is the first report on efficacy psychological intervention protocol on ALS patients. The findings provide initial support for using hypnosis and self-hypnosis training to manage some ALS physical consequences and mainly to cope its dramatic psychological implications for patients and, indirectly, for their caregivers.